Arterial hypertension: A priority challenge for public health in Argentina - Imán , Laura; Imán , Analía (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Arterial hypertension (AHT) is one of the leading causes of morbidity and mortality worldwide. Its asymptomatic nature and severe associated complications, such as cardiovascular disease and stroke, make it a public health priority. In Argentina, the prevalence of HT has increased, facing difficulties such as ignorance of the diagnosis and low adherence to treatment.Development: HT affects 41% of adults over 35 years of age globally and more than 50% in Argentina, with effective control in only 18% of cases. International classifications define HT with blood pressure values ≥140/90 mmHg, distinguishing between primary (with no identifiable cause) and secondary (with demonstrable causes). Although HTN can remain asymptomatic for years, its complications include renal, cardiac, cerebral and ocular damage.The Ministry of Health has implemented programs such as “Less salt, more life” and has developed surveys such as RENATA-2 and ENFR to characterize the problem. Strategies include salt consumption reduction, regular physical activity, health education and access to medication. However, gaps in control persist, especially in adult men due to labor and service access barriers.Nurses play a key role in promoting healthy habits, patient education and treatment monitoring. Models of care such as Orem's self-care theory highlight the importance of a patient-centered approach and educational strategies that promote adherence to treatment.Conclusions: HTA requires a comprehensive approach that combines governmental, community, and primary care efforts. Improving the training of health teams and optimizing resources will make it possible to address this problem more effectively